An Analysis of Merry Riana’s Speech Acts in Alberthiene Endah’s Million Dollar Dream - Raflis, Raflis; Joko Mulyono, Jakarias (Fakultas Sastra Universitas Ekasakti, 2024)
This research is entitled analysis of Merry Riana's speech acts in the novel A Million Dollar Dream by Alberthiene Endah. This research is limited to several main ideas related to observations of the following two questions: what are the types of Riana's speech acts in the Million Dollar Dream Novel and the types of Riana's reference expressions in the Million Dollar Dream Novel. To explain this, the theory used comes from Austin's theory and Kroeger's theory which is used to dissect and get answers to the objectives of this research. For the data analysis method, the author uses a qualitative method by emphasizing the meaning and meaning of Merry Riana's speech acts. This research uses data collection techniques in the form of reading and taking notes. The conclusion in this research is the meaning contained in Merry Riana's speech acts. There are locutionary speech acts, namely speech acts to state something, illocutionary speech acts, namely speech acts that contain hidden meanings or other meanings that the speaker wants to convey to the interlocutor, perlocutionary speech acts are acts of increasing influence or impact on the interlocutor.